Kajian penggunaan xanthomonas cam Pestris pv. Manihotis sebagai pengimbas ketahanan terhadap penyakit karat daun pada kopi arabica=Study of the Use of Xanthomonas canzpestris pv. manihotis as a Resistance Inducer ..... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
Xanthomas competris pv. manihotis and Hemileia vastatrix were spray-inoculated simultaneously and at different time intervals on to one year-old A3 arabica seedlings. The results indicated that the bacterium might cause a reduction of leaf rest intensity, a longer incubation period, less uredospores formation and rechwerl uredospore germination. Variations of Xanthomonas application time resulted in different degree of leaf rust suppression. Inchwerl resistance caused by Xantiwmonas appeared to be local or systemic.